1978
DOI: 10.1172/jci109100
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glucose Augmentation of Insulin Secretion

Abstract: A B S T R A C T Gastric inhibitory polypeptide, or GIP, has been postulated as the major enteric hormonal mediator of insulin release. The release of immunoreactive GIP (IR-GIP) after oral glucose and its role in insulin release was studied in normal men by the glucose clamp technique. In 24 subjects studied with the hyperglycemic clamp, blood glucose was maintained at 125 mg/dl above basal for 2 h via a primedcontinuous IV glucose infusion coupled to a servo-controlled negative feedback system. 40 g glucose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(42 citation statements)
references
References 41 publications
2
39
1
Order By: Relevance
“…In order to investigate further the role of the increased GIP levels in insulin secretion, 5-g IV glucose injections were given 1 h after the oral ingestion of lentils with or without fat. The intravenous injection raised plasma glucose levels above the reported threshold necessary for GIP to potentiate insulin secretion [21]. However, the insulin response was not affected by co-ingestion of fat, despite large differences in GIP levels.…”
Section: Discussionmentioning
confidence: 86%
“…In order to investigate further the role of the increased GIP levels in insulin secretion, 5-g IV glucose injections were given 1 h after the oral ingestion of lentils with or without fat. The intravenous injection raised plasma glucose levels above the reported threshold necessary for GIP to potentiate insulin secretion [21]. However, the insulin response was not affected by co-ingestion of fat, despite large differences in GIP levels.…”
Section: Discussionmentioning
confidence: 86%
“…In adults, GIP-stimulated insulin response has been shown to be glucose dependent (17). An incremental glucose rise of 1' 7 mg/dL over fasting, or a threshold plasma glucose concentration of 105 mg/dL or g r a t a was required (18) for GIP-mediated enhanced insulin response to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The normal GIP response after oral glucose might be the result of suppression by the concomitant hyperinsulinism excerting a negative feedback control on GIP release. However, it has been shown that insulin does not suppress glucose induced GIP release [11]. Another possibility is that the utilization of nonesterified free fatty acids by the GIP cell may interfere with GIP secretion [12].…”
Section: Discussionmentioning
confidence: 99%